Fullfillment Of Educational Rights For Woman Through Women’s Schools In Aengbaja Kenek Village - Devi Mutiara Sanni; Basuki Babussalam (Faculty of Law, Muhammadiyah University of Surabaya, 2022)
This research wants to highlight the fulfillment of women's educational rights as regulated by the 1945 Constitution. This research will answer the questions (1) How is the implementation of the fulfillment of educational rights stated in the 1945 Constitution? (2) How is the right to education fulfilled through women's schools in Aengbaja Kenek Village ? This research uses empirical research methods, namely by conducting interviews, Focus Group Discussions and several other relevant literature. The research results show that, First, the fulfillment of educational rights in Indonesia has not been maximized, especially for women. Second, the fulfillment of education as regulated by the 1945 Constitution is still limited to the high school level. Third, in Aengabaja Kenek village, they still adhere to the old rules, namely that women are limited to a kitchen, well and mattress. Fourth, women after high school education must be required to work, some are even forced to get married immediately. The research methods used were in-depth interviews, participant observation, and questionnaires. The results of the research show that the majority of women in Aengbajakenek village still adhere to old cultures that limit women's educational rights, namely that women are limited to being housewives. Apart from that, the research results also show that women's schools in villages have a crucial role in facilitating women's access and participation in safe and inclusive education for women, helping overcome gender stereotypes, including increasing awareness of their rights. However, this research also identified several challenges, such as women's lack of awareness to fulfill their own needs in fulfilling their education, gender stereotypes that still occur in society, and cultural norms that inhibit women's full participation in education. Therefore, further efforts are needed to strengthen women's schools, build public awareness about the importance of women's education, and promote gender equality at all levels of society in Aengbajakenek village, Sumenep, Madura.